EFEKTIVITAS PELAKSANAAN PROGRAM GANGGUAN PSIKOTIK DI RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Fadizah Marfuatul Arifah; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The handling of psychotic homeless social problems in the border and urban areas is carried out to find out how far the management efforts of psychotic larvae sufferers in order not to become homeless by the technical service and the community itself. Psychotic bums are people who experience psychiatric disorders roaming the streets. The Handsome Mental Hospital of Pekanbaru City has a duty of community service, and carries out the duty as a Mental Hospital to treat Mental Disorders and all of that has been regulated in Riau Province Regulation No. 18 of 2002, concerning the Establishment of the Organization and Work Procedures of the Handsome Mental Hospital of Pekanbaru City. The phenomena that occur are there are still many mental psychotic patients roaming the streets and crowded centers, and other facts in the field that there are still psychotic patients in their families at home so that they are not ashamed of their neighbors, and facts in the field others still lack the comparison of the number of nurses with the number of psychotic patients themselves. The purpose of this study was to determine the effectiveness of the implementation of the Psychotic Disorders Program at the Handsome Mental Hospital of Riau Province. This research was conducted at the Tampan Mental Hospital of Riau Province with a descriptive method, the data collected through observation and interviews. This research was conducted by using Gibson's theory in Abdul Sadad where variables in measuring effectiveness consist of Input, Process and Output. The results of the study showed that the effectiveness of the implementation of the Psychotic Disorders Management Program in the Handsome Mental Hospital of Riau Province was less effective. It was seen from the effectiveness inputs that there were deficiencies in the process, namely program socialization which was still not felt by the community at the time the program was implemented. The factors that influence the effectiveness of the implementation of the Psychotic Disorders Program at the Handsome Mental Hospital of Riau Province, namely the coordination and evaluation of the program Keywords: Effectiveness, Psychotic, Mental Hospital